Models of rotating coronae - Sormani, Mattia C.; Klessen, Ralf S. (Monthly notices of the Royal Astronomical Society, 2018)
Fitting equilibrium dynamical models to observational data is an essential step in understanding the structure of the gaseous hot haloes that surroun
Gesehen am 06.08.2020